The Comparison and the Presentation of Data in the Economical Statistics - Valkauskas, Romualdas (Ekonomika, 2002)
The comparison and the presentation of data in the economical statistics is complicated problem. This problem is important for practice of statistics and for science of statistics. The comparison and the presentation of data is one case the problem of the theory of economics statistics. It is problem the accuracy data of economics statistics. This problem can be separate into two cases: accuracy of the count in microeconomics and accuracy of the count in macroeconomics. In the article made the discus about the main of reasons the comparison of economics statistics data. Show the mains of methods try to reach the comparison of data. Show the role tables and graphics to presentation processes of macroeconomics and micro economics. We separate graphs into three cases: graphs to imagine the facts, graphs to imagine the additional computed data and the standards graphs.